Medieval Manuscripts in Marsh's Library: An Unintended Collection in Dublin's First Public Library. - Cleaver, Laura; MaGnusson, Danielle; Tookey, Isabel (Manuscript Studies: A Journal of the Schoenberg Institute for Manuscript Studies)
Narcissus Marsh began planning a public library for Dublin at the end of the seventeenth century. By 1704, a library building had been constructed near Saint Patrick's Cathedral, and Marsh turned his attention to its contents. He planned a collection of 10,000 books "with none but ye most usefull Books in each Faculty and Science." Marsh was prepared to buy books from London and the Continent and sought advice on what the most appropriate new titles for his library might be. He bought books individually and en bloc , including volumes from the library of the Dublin scholar Dudley Loftus. However, he recognized that buying collections risked adding books that he did not want. Marsh deliberately bought what he called "Oriental" manuscripts, which he left to the Bodleian Library, but a few European volumes remained in Dublin. Among the volumes acquired from Loftus that did not obviously fit Marsh's plan were a small number of medieval manuscripts. More medieval books were added when, in 1701, Marsh recruited a Huguenot refugee, Elie Bouhéreau, as librarian for the new collection, with the agreement that he give his books to the library. In the following century, further manuscripts were given by Church of Ireland clergymen. Although the twenty-three volumes of medieval manuscripts now at Marsh's Library form but a tiny part of the overall library, they provide insights into of the roles of intention, opportunity, and personal choice in the formation of this early modern library, which in turn ensured the survival of some medieval manuscripts.